2008
DOI: 10.1016/j.pain.2008.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Pain intensity influences the relationship between anger management style and depression

Abstract: There is an abundance of studies concerning depression and pain, while the mechanisms and the relationships of anger expression and pain are less well known. The validity of commonly used depression questionnaires as measures of depression in pain patients has been questioned, as they include items which can be related to the pain problem as well as to signs of depression. The aim of this study was to investigate the relationships between pain severity, various signs of depression, and anger management style. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
8
1
Order By: Relevance
“…Emotions such as anger, frustration, fear, and sadness often occur simultaneously with depression in patients with CMP 14. The psychiatric evaluation in this study revealed that approximately 90% of patients who were sick-listed due to somatic diagnoses had mental health comorbidity that was not diagnosed before this consultation.…”
Section: Discussionmentioning
confidence: 68%
“…Emotions such as anger, frustration, fear, and sadness often occur simultaneously with depression in patients with CMP 14. The psychiatric evaluation in this study revealed that approximately 90% of patients who were sick-listed due to somatic diagnoses had mental health comorbidity that was not diagnosed before this consultation.…”
Section: Discussionmentioning
confidence: 68%
“…In line with the action-control framework of parental self-regulation (Dix and Meunier, 2009), we hypothesize that co-occurrence of cognitive-affective depression and nonspecific somatic symptoms in the DSS cluster are linked with overreactive interpersonal interactions through its association with additional explanatory mechanisms, such as negative emotional arousal and dysregulation. Maternal anger hyperactivity may particularly operate as a key explanatory mechanism of these associations (Estlander et al, 2008). Conceptual frameworks suggest anger as a primary emotional reaction to physical and affective pain (Bruehl et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Despite being informative, initial formulations of this framework did not account for the overlapping of cognitive-affective depressive and specific and/or nonspecific somatic symptoms in those regulatory processes. However, a large body of research has shown strong associations between nonspecific somatic symptoms and negative emotional arousal and emotional dysregulation in women, including anger dysregulation (Estlander et al, 2008), higher irritability (Tikotzky, 2016), affective volatility (Dinges et al, 1997), lower threshold to frustration (Massey et al, 2009), and fear dysregulation (Seng et al, 2006). Drawing from these previous contributions, a plausible thesis is that the overlap of cognitive-affective depressive and nonspecific somatic symptoms might have a differential impact on the cognitive-affective regulatory processes that determine parenting and coparenting.…”
Section: Depressive-somatic Symptoms Parenting and Coparentingmentioning
confidence: 99%
“…However, patients often experience discomfort following DT. When a lesion is found on the oral mucosa following any form of DT, it tends to be attributed to the DT a patient previously received (11,12). A variety of stimuli may be applied to the oral mucosa during DT, and patients with earlystage OMLs may be exposed to these stimuli, resulting in altered oral epithelia, which can lead to worsening of the mucosal disease.…”
Section: Discussionmentioning
confidence: 99%